APLIKASI SISTEM PAKAR UNTUK MENDIAGNOSIS PENYAKIT KUSTA DENGAN METODE FORWARD CHAINING - Kurnia Cahyana, Muhammad Angga; Simanjuntak, Pastima (Computer Science and Industrial Engineering, 2020)
Leprosy, known as leprosy or hansens disease, is a disease that attacks the skin, the peripheral nervous system, the linning of the upper respiratory tract, and the eyes. Leprosy can cause skin injuries, nerve damage, muscle weakness, and numbness. Leprosy is caused by the bacterium Mycobacterium Leprae. This bacterium takes 6 months to 40 years to develop in the human body. Signs and symptoms of leprosy can 1 to 20 years after the bacteria infect the patients body. The goal achieved in this research is to make an application of an expert system that is useful to help obtain information and initial allegations in the diagnosis of leprosy. For this study using the forward chaining method. Forward chaining is a search technique that starts from known fact and then matches the fact with the if part of the IF-THEN rules. The results of this study are that the public, especially patients with leprosy, can solve the problem of leprosy and can provide temporary solutions and alternative treatments for leprosy.